Transboundary Haze and the Call for a Global Forest Convention - Arjuna, Hendra; Thahira, Atika (GoAcademica Research & Publishing, 2025)
Existing global agreements related to forest governance indicate that the current approach centered on promoting synergy among various instruments is insufficient to address the persistent regulatory gaps. One of the most pressing issues is the recurring transboundary air pollution caused by forest fires in Indonesia, which significantly affects neighboring countries. Indonesia’s tropical rainforests, often dubbed the lungs of the world, contribute to approximately 40% of the earth’s oxygen supply, underscoring their global environmental importance. Despite the existence of numerous international treaties that partially regulate forest-related activities, there remains no single, comprehensive international legal instrument that fully integrates all three pillars of sustainable development environmental, social, and economic in the context of forest ecosystems. This study employs a doctrinal legal research method using statutory, conceptual, and case study approaches. It concludes that the fragmented and sectoral nature of existing agreements hinders the achievement of sustainable forest management. Accordingly, this article advocates for a paradigm shift by expanding the scope and mandates of existing frameworks such as the Convention on Biological Diversity (CBD) and the World Trade Organization (WTO) to explicitly include sustainable forest governance. Furthermore, the article emphasizes the importance of cooperative mechanisms in addressing transboundary hazardous air pollution and proposes the establishment of a single, unified international convention on forests. Such a convention would provide a holistic and legally binding framework to strengthen forest protection, promote sustainable use, and enhance international collaboration.